Prevalence of icaA and icaD genes in Staphylococcus aureus and Staphylococcus epidermidis strains isolated from patients and hospital staff - Satorres, Sara Elena; Alcaráz, Lucia Esther (Central European journal of public health, 2007)
Staphylococci are ubiquitous microorganisms that predominate in normal skin and mucosal flora. Staphylococcus aureus and Staphylococcus epidermidis have been identified as a major cause of nosocomial infections, especially in patients with predisposing factors such as indwelling or implanted foreign bodies. The ability of both S. epidermidis and S. aureus to produce biofilm was compared between 116 clinically significant strains (46 from blood cultures of patients with bloodstream infection and 70 isolated from catheters) and 60 strains isolated from nasal swabs of healthy carriers from hospital staff. The presence of the intercellular adhesion genes (icaA and icaD) was determined by the Polymerase Chain Reaction method, and slime production was examined using qualitative Congo red agar technique. Among clinical strains, 35.2% (19/54) of S. aureus and 48.4% (30/62) of S.epidermidis were both positive icaA and icaD and they produced slime. Among carrier strains, 22.2% (8/36) of S. aureus and 33.3% (8/24) of S. epidermidis were positive for slime synthesis and exhibited ica genes. Our results suggest that the virulence factors contributing to the development of infections can be present in patient and hospital staff isolates. Thus, we consider it is important to detect healthy carriers of slime-producing staphylococci and to control the dissemination of these microorganisms especially in a hospital.
Keywords: Staphylococcal Infections; Staphylococcus aureus; Personnel, Hospital; Humans; sekvence nukleotidů; stafylokokové infekce; pacienti; Kongo červeň; lidé; Culture Media; kultivační média; Cell Adhesion Molecules; Base Sequence; biofilmy; molekuly buněčné adheze; Patients; personál nemocniční; polymerázová řetězová reakce; Polymerase Chain Reaction; Congo Red; Staphylococcus epidermidis; Biofilms